Temporal and spatial differences in the reproductive biology of the sea urchin Arbacia dufresnii - Epherra, Lucía (2014)
The reproductive cycle of Arbacia dufresnii was studied in two contrasting populations on the eastern coast of Patagonia (Nuevo Gulf and San Jorge Gulf) from January 2008 to August 2010. Sea urchins from San Jorge Gulf had larger test diameter and heavier gonads than did sea urchins from Nuevo Gulf. A. dufresnii showed an annual cycle in both populations, with gametogenesis occurring mainly in the autumn and the winter. An extended spawning period took place during the spring and the summer. Sea urchins from Nuevo Gulf had a strong seasonal pattern of reproduction, with presence of gonadal stages showing re-absortion and accumulation of reserves in nutritive cells at different seasons, whereas individuals from San Jorge Gulf had mature gametes during most of the year. Interannual variation of seawater temperature affected the gamete production and spawning duration in both populations. Higher temperatures during gametogenesis enhanced gonadal growth and gametes were released early. The major population differences found in gonadal cell composition highlight the plasticity in reproductive traits of A. dufresnii, and may be responsible for the wide distribution of A. dufresnii in different environments.